Peningkatan keterampilan berbicara melalui penerapan model pembelajaran academic-constructive controversy pada peserta didik kelas IV sekolah dasar - Marfuah Dwi Sarwanti (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
The purpose of this research is to improve speaking skills by applying a collaborative learning model. This research is a Classroom Action Research with three cycles. The subjects of this study were the fourth grade students of SD Negeri Kerten II Surakarta in the academic year 2019/2020 with a total of 13 students. This research uses data collection techniques in the form of interviews, observations, field notes, tests, and documentation with data analysis of content validity and triangulation. Analysis of the data used is the interactive analysis of the Miles- Huberman model. The first cycle produces an average indicator of 39.26 and the study continues with the second cycle with an average of 50.92 until the third cycle has an increase of 64.15 Based on the results of the study, it can be included that the speaking skills in fourth grade students of Kerten II Elementary School Surakarta in the academic year 2019/2020 can be improved through the type of collaborative learning model Academic Constructive Controversy. The result of this study have contributed to the world of education as one alternative to solving the affective realm, especially social attitudes of cooperation.